2018
DOI: 10.5114/jos.2018.84763
|View full text |Cite
|
Sign up to set email alerts
|

Oral health literacy among adults in Jakarta, Indonesia

Abstract: Introduction: There is an emerging need to improve oral health literacy (OHL) for good oral health outcomes worldwide. Many OHL tools have been developed, and the Indonesian version of Health Literacy in Dentistry (HeLD-ID) has the potential to be a valid and reliable oral health instrument for use in Indonesia. Objectives: We aimed to measure OHL using HeLD-ID and to analyze the socioeconomic determinants of OHL among adults in Jakarta. Material and methods: In total, 1000 adults representing five regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…15 HeLD consists of seven domains including Receptivity, Understanding, Support, Economic Barrier, Access, Communication, and Utilization. 9 Several previous studies have examined the impact of OHL on oral health status and behavior. They indicate that there is a significant relationship between high OHL and overall oral health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 HeLD consists of seven domains including Receptivity, Understanding, Support, Economic Barrier, Access, Communication, and Utilization. 9 Several previous studies have examined the impact of OHL on oral health status and behavior. They indicate that there is a significant relationship between high OHL and overall oral health.…”
Section: Discussionmentioning
confidence: 99%
“…5 There are many tools available to measure OHL, and one of them is Health Literacy in Dentistry (HeLD) questionnaire. 9 The benefit using HeLD questionnaire besides it concerns in cultural appropriateness, it also covers more domains such as communication, access, economic barriers, receptivity, understanding, utilization, and support. 9 Based on previous study, HeLD questionnaire has been translated into Indonesian Language (HeLD-ID) and showed as a potential to be a valid and reliable oral health instrument particularly in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a study in 2018 in Jakarta, the oral health literacy rate decreases with age. This is influenced by several factors, such as mental health, reading ability, health status, and vision 22 .…”
Section: Discussionmentioning
confidence: 99%